Later-Line Treatment with Lorlatinib in ALK- and ROS1-Rearrangement-Positive NSCLC: A Retrospective, Multicenter Analysis - Maximilian J. Hochmair; Hannah Fabikan; Oliver Illini; Christoph Weinlinger; Ulrike Setinek; Dagmar Krenbek; Helmut Prosch; Markus Rauter; Michael Schumacher; Ewald Wöll; Romana Wass; Elmar Brehm; et al. (MDPI AG, 2020)
In clinical practice, patients with anaplastic lymphoma kinase (ALK)-rearrangement-positive non-small-cell lung cancer commonly receive sequential treatment with ALK tyrosine kinase inhibitors. The third-generation agent lorlatinib has been shown to inhibit a wide range of ALK resistance mutations and thus offers potential benefit in later lines, although real-world data are lacking. This multicenter study retrospectively investigated later-line, real-world use of lorlatinib in patients with advanced ALK- or ROS1-positive lung cancer. Fifty-one patients registered in a compassionate use program in Austria, who received second- or later-line lorlatinib between January 2016 and May 2020, were included in this retrospective real-world data analysis. Median follow-up was 25.3 months. Median time of lorlatinib treatment was 4.4 months for ALK-positive and 12.2 months for ROS-positive patients. ALK-positive patients showed a response rate of 43.2%, while 85.7% percent of the ROS1-positive patients were considered responders. Median overall survival from lorlatinib initiation was 10.2 and 20.0 months for the ALK- and ROS1-positive groups, respectively. In the ALK-positive group, lorlatinib proved efficacy after both brigatinib and alectinib. Lorlatinib treatment was well tolerated. Later-line lorlatinib treatment can induce sustained responses in patients with advanced ALK- and ROS1-positive lung cancer.